PENERAPAN MODEL MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR GEOGRAFI DI KELAS X SMAN 1 AMBAWANG - Rohimah, Rohimah; Asriati, Nuraini; Parijo, Parijo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the application of make a match learning model in improving learning outcomes of class X IIS SMA Negeri 1 Sungai Ambawang. The method used in this study is quasi-experimental with a type of quantitative research. Sources of data in this study were students of class X IIS where class X IIS 1 amounted to 32 students as an experimental class and class X IIS 3 amounted to 32 as a control class. Data collection techniques using observation techniques and measurement techniques, while the data collection tools used are observation sheets and written tests in the form of multiple choices totaling 30 questions. Based on the results of the average value of the control class and experimental class has a difference. The results of the data calculation obtained the average value of the post-test control class was 54.85 while the average value of the post-test experimental class was 66.97. From the data it can be seen that the average post-test value is higher than the class control class. This shows that the application of the make a match learning model can improve student learning outcomes. This is also evidenced by the student learning outcomes of the experimental class and the control class which has a difference of 12,123. Keywords: Make a match, learning outcom,  geografi learning